PENGARUH KEGAGALAN DAN PEMULIHAN SELF SERVICE TECHNOLOGY TERHADAP ONLINE SHOPPING EXPERIENCE, SATISFACTION DAN REPURCHASE INTENTION: SEBUAH TINJAUAN DALAM PERSPEKTIF CRITICAL SDL - Stiawan, Evan (Institut Agama Islam Bengkulu, 2016)
There are rooms where producers and consumers do not meet to create value in use. The existence of a Joint sphere to create co-creation value raises the importance of the customer experience. At a time when the world has changed with characteristics where transactions are done facilitated by technology. This results in less interaction between employees and customers to create results from services in self-service technology. Service failure is important because service failure is one of the causes that drive customers to move to other companies in meeting their needs. Then the relationship between service failure and customer satisfaction can be explained by looking at initial disconfirmation and recovery disconfirmation. The customer's expectation of a possible problem is confirmed as well as the customer's expectation of a viable recovery effort, thereby creating a buy back for the consumer. This proposition aims to contribute theories about the effects of SST quality on the customer experience of shopping using online services, the effect of quality of SST on customer satisfaction shopping using online services, the effect of customer experience shopping using online services to customer satisfaction shopping using online services, Effect of SST failure on customer satisfaction shopping using online services, customer satisfaction effects shopping using online services to the intention of repurchase in shopping using online services with mediation from recovery from failure to shop using online servicesKeywords: Self Service Technology, Online Shopping Experience, Satisfaction and Repurchase Intention, Critical SDL